(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2026)
This study was conducted to scientifically document indigenous knowledge and practices of soil fertility management and nutrient cycling in five different agroforestry-based farming systems (AbFS) in the Eastern Himalaya -Hee-Bermiok-Uttarey (800-2100 m), West Sikkim; Dzongu (600-2000 m), North Sikkim; Lingi-Sokpay (500-2000 m), South Sikkim; and Pendam (500-2000 m), East Sikkim. The research involved a mixed-methods design that combined biophysical and ethnographic assessments through focus group discussions, household surveys, participatory field investigations, and soil nutrient analysis. The main inventory of traditional practices of soil fertility management (TPSFM) included farmyard manure (FYM) preparation, in situ manuring, mulching with forest litter and crop residues, green manuring, controlled biomass burning, incorporation of N2-fixing plants, ash application, silt trapping, and periodic land fallowing. FYM and bio-compost application were the most dominant practices while livestock integration was significant to nutrient cycling and microbial enrichment. Soil physico-chemical attributes across AbFS revealed substantial variation, with cardamom-based, farm-based and mandarin orange-mix tree-based agroforestry exhibiting higher total-N, total-P, available-P, and organic-C with enhanced soil moisture and optimal bulk density, which indicated high nutrient cycling efficiency and structural stability. These indigenously time-tested, low-input agroecological systems sustained adequate soil fertility, increased organic matter turnover, and reinforced the adaptive capacity of ecosystems. The research findings demonstrated that the practice of traditional AbFS represent scientifically grounded, low-carbon, and biodiversity-supportive model of sustainable agriculture. Integrating indigenous agroecological knowledge into development programs and policy frameworks is vital for advancing climate-resilient, economically inclusive, as well as agro-ecologically and agro-climatically sound farming systems, thereby scientifically validating the TEK of indigenous communities.